Linked color imaging improves the visibility of colorectal polyps: a video study - Yoshida, Naohisa; Naito, Yuji; Murakami, Takaaki; Hirose, Ryohei; Ogiso, Kiyoshi; Inada, Yutaka; Dohi, Osamu; Kamada, Kazuhiro; Uchiyama, Kazuhiko; Handa, Osamu; Konishi, Hideyuki; Siah, Kewin Tien Ho; Yagi, Nobuaki; Fujita, Yasuko; Kishimoto, Mitsuo; Yanagisawa, Akio; Itoh, Yoshito (Endoscopy International Open, 2017)
Background/study aim Linked color imaging (LCI) by a laser endoscope (Fujifilm Co, Tokyo, Japan) is a novel narrow band light observation. In this study, we aimed to investigate whether LCI could improve the visibility of colorectal polyps using endoscopic videos.Patients and methods We prospectively recorded videos of consecutive polyps 2 – 20 mm in size diagnosed as neoplastic polyps. Three videos, white light (WL), blue laser imaging (BLI)-bright, and LCI, were recorded for each polyp by one expert. After excluding inappropriate videos, all videos were evaluated in random order by two experts and two non-experts according to a published polyp visibility score from four (excellent visibility) to one (poor visibility). Additionally, the relationship between polyp visibility scores in LCI and various clinical characteristics including location, size, histology, morphology, and preparation were analyzed compared to WL and BLI-bright.Results We analyzed 101 colorectal polyps (94 neoplastic) in 66 patients (303 videos). The mean polyp size was 9.0 ± 8.1 mm and 54 polyps were non-polypoid. The mean polyp visibility scores for LCI (2.86 ± 1.08) were significantly higher than for WL and BLI-bright (2.53 ± 1.15, P < 0.001; 2.73 ± 1.47, P < 0.041). The ratio of poor visibility (score 1 and 2) was significantly lower in LCI for experts and non-experts (35.6 %, 33.6 %) compared with WL (49.6 %, P = 0.015, 50.5 %, P = 0.046). The polyp visibility scores for LCI were significantly higher than those for WL for all of the factors. With respect to the comparison between BLI-bright and WL, the polyp visibility scores for BLI-bright were not higher than WL for right-sided location, < 10 mm size, sessile serrated adenoma and polyp histology, and poor preparation. For those characteristics, LCI improved the lesions with right-sided location, SSA/P histology, and poor preparation significantly better than BLI.Conclusions LCI improved polyp visibility compared to WL for both expert and non-expert endoscopists. It is useful for improving polyp visibility in any location, any size, any morphology, any histology, and any preparation level.Study registration: UMIN000013770